Effect of short and long period of salinity stress on physiological responses and biochemical markers of Aloe vera L. - Mandana Mirbakhsh; Sara Sohrabi sedeh (Jurnal Ilmu Pertanian, 2022)
Salinization reduces soil health and quality, drastically limiting growth and reducing land degradation and crop yield. This comprehensive research aimed to evaluate the impact of sodium chloride increment on growth factors, amount of oxidative stress biomarker (Malondialdehyde), osmotic response (evaluated by both proline and sugars contents), photosynthesis efficiency (expressed with chlorophyll fluorescence measurement) and activity of Malate dehydrogenases (MDHs) as a regulator under abiotic stress tolerantly in Aloe in Alzahra University, Tehran. Experiments were conducted in two studies at the following concentration of sodium chloride: 0 (control), 100, 200, and 300 (mM) NaCl for 30 days (short-term treatments) and: 0 (control), 54.7, 109.5, and 164.5 (mM) NaCl for 150 days (long-term treatments). Three replications in completely randomized design were applied. The results showed that while the fresh weight of belowground biomass declined at higher salinity level (164.5 mM), no significant differences were reported in the short period of salt treatments. A considerable amount of free proline was accumulated in both short (3.594 µg.g-1 dw) and long ( 2.20 µg.g-1 dw) term studies which raised the role of proline in osmoregulation. Our results showed the decline of MDA amount (0.0003mmol.g-1FW) in 54.7 NaCl (mM) that may be due to less membrane damage in presence of moderate salinity, indicating a variety of dependent differences in biochemical markers activity.